Comportamiento en el suelo de herbicidas residuales selectivos en los citricos - Gomez de Barreda, D.=700 1 Lorenzo, E.; Ramos, C.; Del Busto, A.; Carbonell, E.A.; Gamon, M.; Saez, A.; Garcia de la Cuadra, J.
(Es, En)
ilus., 4 ref.
Keywords: CITRUS; PERSISTENCIA DE LOS PLAGUICIDAS; BROMACILO; DIURON; ESPAÑA; CITRICOS; TRIAZINAS; HERBICIDAS RESIDUALES